A rare presentation of plexiform neurofibroma - Poh, Khay Wei; Syed Osman SIH (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
We report on a rare case of a child with persistent right upper lid eversion with conjunctival prolapse since birth that failed various attempts in repositioning the right superior fornix at other centre. He was found to have a right supero-temporal orbital mass above the prolapsed area. Computerized tomography (CT) scan of orbit confirmed a right lacrimal gland tumour with thinning of the right lesser wing of sphenoid. An excision biopsy of the tumour via anterior orbitotomy and eyelid reconstruction were performed. Histopathology report reviewed plexiform neurofibroma of the lacrimal gland. Further physical examination confirmed presence of multiple café-au-lait spots. He was diagnosed as Neurofibromatosis Type 1.